(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Determining the prevalence of overweight and obesity among students at Tran Hung Dao Primary School, Thai Binh City, in 2025. Method: From August 2024 to August 2025, a cross-sectional study was conducted on 1123 students from grades 1 to 5 in the school. Results: The prevalence of overweight and obesity among students at the study site was 35.7% (overweight 21.3%; obese 14.4%); of which males accounted for 46.6%; females accounted for 24.4%. Conclusion: The prevalence of overweight and obesity among students at Tran Hung Dao Primary School is on the rise and requires appropriate attention. This necessitates strengthening communication and education activities on nutrition for both parents and students, while simultaneously guiding the formation of healthy eating habits and increasing physical activity for children to reduce the risk of overweight and obesity.